Penghimpunan Dana Zakat Infak Sedekah Berdasarkan Intensi Perilaku Muslim Gen Y dalam Penggunaan Teknologi Digital Payment - Rachmat; Lukman M. Baga; Ninuk Purnaningsih (AL-MUZARA'AH, 2020)
The development of lifestyle generation Y is inseparable from technological development. That changes the behavior of gen Y Muslims in making zakat, infaq, shodaqoh (ZIS) payments from conventional to digital. The purpose of this study is to describe the characteristics of Muslim gen Y related to digital ZIS payments, then to analyze what influences the behavior intention of gen Y Muslims in the use of digital payment technology for ZIS payments. The results of this study qualitatively indicate that the characteristics of digital payment technology users for ZIS payments are dominated by female gen Y Muslims. The most commonly used digital payment method is transfer via mobile banking and via e-wallet. Digital service partners that are widely used to channel digital ZIS payments to OPZ are banking institutions. The quantitative research results show that the overall variables studied, namely performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), hedonic motivation (HM), price value (PV), habit (HT), and perceived security (PS) have a significant influence on the behavioral intention (BI) of gen Y Muslims in the use of digital payment technology for ZIS payments, where the greatest factor influences the intention of gen Y Muslims behavior is perceived security.